Mengapa Perusahaan Anjak Piutang kurang berkembang di Indonesia? (Dilihat dengan analisis Risk profile, Good Governance, Earning dan Capital (RGEC)) - Rani Eka Diansari; Vidya Vitta Adhivinna (Akademi Akuntansi YKPN Yogyakarta, 2019)
Factoring Company is one of the financial institutions in Indonesia. Factoring Company is a company that serves to take over the receivables that occur in buying and selling transactions so as not to cause serious problems in the company's cash flow. Risk can be avoided very minimally and the company can greatly help avoid a problem related to its uncollectible trade through financial institutions with factoring concept (Aprianto, 2017). Based on the concept of factoring, actually the existence of the company factoring is very profitable for companies especially trading companies, but if looking at the data in Indonesia is still very little of the company's sustainability factoring, the evidence can be seen on the Indonesian stock exchange, with less than 100 companies factoring listed on the stock exchanges. It shows that in Indonesia the company factoring is very less developed.With these conditions, the author is interested to see the cause of the company factoring is not developed well from the analysis of risk profile, good governance, earning and Capitalnya, although RGEC is prevalent in banking industry but because Consideration of the activities of the company to be receivables some have the same characteristics as banking then the authors tried to analyze with RGEC analysis by the detailed risk profile not only based on the ratio of LDR and NPL Were. The object in this study was the factoring company listed on the Indonesia Stock exchange in 2017 and examined by a qualitative method of descriptive. Results of the research can be concluded there are several factors that cause the company to factor less developed in Indonesia including the inherent risk of credit, human resources, regulation, and public trust because the factoring isn't famous.